Quality of life in dialysis versus kidney transplantation - Abdelfatah, Mahmoud; Shawky, Sahar; Azzab, Eman (African Journal of Nephrology, 2010)
<p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Introduction: The compromised health-related quality of life (HRQOL) of patient with end-stage renal disease(ESRD) is now well documented. One of the main pointswhen treating patients with ESRD, whose cure is not arealistic goal, is maximizing functioning and well-being,which refer to the ability to perform various dailyactivities and functions and to more subjective internalstates such as symptoms and feelings. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Aim: Is to study the difference in QOL between dialysispatients and living renal transplant recipients using SF-36 Health survey and factors affecting QOL. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Setting and participant: Seventy patients were includedin our study 34 of them were males and 36 females. Theywere divided into 3groups: Group Ia: 30 hemodialysispatients of at least 6 months duration on dialysis, GroupIb: 10 continuous ambulatory peritoneal dialysis (CAPD)and Group II: 30 recipients of living renal transplants of? 6 months duration. SF-36 questionnaire was filled byall patients; it includes eight subscales which can also becombined into two component summary scores, Aphysical component summary PCS general heath (GH),physical function (PF), role-physical (RP), bodily pain(BP) and a mental component summary MCS roleemotional(RE), vitality (VT), mental health (MH), andsocial function (MH). Data were analyzed from thisquestionnaire to determine the QOL for all patients andwere correlated also with clinical and laboratoryparameters. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Results: Among hemodialysis patients, PCS, PF and VTparameters were better in young subjects and MH waspositively correlated with the hemoglobin level. Patientswithout co-morbid conditions had significantly betterQOL in PF and RP parameters. QOL was significantlybetter in employed than unemployed persons regardingPF, RP, VT, SF, GH and PCS. As regard CAPD patients without co-morbid conditions had significantly better QOL than those with co-morbid condition regarding RP, GH, SF and PCS. Among recipients of renal transplantation, there was a significant positive correlation between hemoglobin level and QOL parameters PCS, MCS, VT, SF and MH and a significant negative correlation between age of transplanted recipients and PF and VT was recorded. Finally in comparison of the three studied groups there was significant difference between the studied groups as regard PF parameter of SF-36 health survey which was higher in transplanted group than HD and CAPD. <p style="margin: 4px; color: #000000; font-family: ’Merrieweather sans’, sans-serif; font-size: 12.6px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: left; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial;">Conclusion: In hemodialysis patients the best quality of life was to males young aged with high hemoglobin level and no co-morbid conditions. In CAPD the best quality of life was to young aged and no co-morbid conditions. In renal transplant the best quality of life was to young age and high hemoglobin level. Finally there was no difference in QOL with three forms of renal replacement therapy.